2004
DOI: 10.1103/physreva.70.013810
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies for the single-mode operation of a quantum optical nonlinear shift gate

Abstract: We investigate the single-mode operation of a quantum optical nonlinear phase-shift gate implemented by a single two-level atom in one-dimensional free space. Since the single-mode property of the input photons at the atom is not preserved in the interaction at the atom, we analyze the efficiency of single-mode operation that can still be achieved. We show how the input pulse shape can be optimized to obtain high efficiencies for the nonlinear single-mode operation. With this analysis, we obtain an optimal sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…The interference is destructive because the fluorescence field emitted by a two-level system is phase-shifted by π with respect to the driving field as pointed out by Kojima [20]. If the dipole is not resonant with the cavity the transmission is a Fano resonance as underlined by Fan [19].…”
Section: A Linear Regime : Dipole Induced Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference is destructive because the fluorescence field emitted by a two-level system is phase-shifted by π with respect to the driving field as pointed out by Kojima [20]. If the dipole is not resonant with the cavity the transmission is a Fano resonance as underlined by Fan [19].…”
Section: A Linear Regime : Dipole Induced Reflectionmentioning
confidence: 99%
“…Unfortunately recent results suggest that this may not be possible. A numerical study [20] found fidelities of quantum gates employing the present non-linearity of order 80 %, which is quite far from what would be desirable for quantum computing or even quantum communication. Higher fidelities are elusive because the interaction with the single two-level system introduces temporal correlations between the two input photons.…”
Section: Perspectivesmentioning
confidence: 99%
“…We consider the case where the continuum of modes has only one direction of propagation, so that the atom can only emit light in one direction as in [10]. This semiinfinite waveguide model could correspond, in principle, to a physical situation where a mirror [24], or a metallic nanotip [12], is placed close to the atom, just to mention potential realizations.…”
Section: Arxiv:12085817v1 [Quant-ph] 29 Aug 2012mentioning
confidence: 99%
“…In particular, they provide optical non-linearities at the single photon level [7][8][9], paving the road towards the implementation of efficient photonic gates [10]. At the same time, light emitted by the atom interferes with the pump, leading to interesting phenomena like dipole induced reflection [8] or super-bunching in the transmitted light [7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the tapered fiber system as opposed to other fiber-coupling architectures, e. g. end-facet coupling [18], allows for measurements in transmission. This is a requirement for the implementation of single photon nonlinearities [39], single photon transistors [40] or quantum phase gates [41,42].…”
mentioning
confidence: 99%